Guernsey : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
Bailiwick of Guernsey has a Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) legal framework that provides the basis for an AML/CFT regime. It has a program to review and enhance AML/CFT legislation and monitor effectiveness of compliance with the AML/CFT regime. Assessors found that confiscation and provisional measures within Bailiwick are robust. They also found that previous designation mechanisms had a negative impact on the effectiveness of the mutual legal assistance system. The assessors recommended to enhance the requirements for the freezing and confiscation of terrorist assets, and also provided guidance.